As relações com saberes de biologia em falas de jovens alunos do ensino médio a partir do ensino de biologia : uma visão sociocultural - Alves, Victor Cherubin (Universidade Federal de São Carlos, 2016)
This research aims to analyze the relationship with knowledge, including biology, that the students explicit in the school context. It is based theoretically in studies of Charlot (2000, 2001, 2005, 2015) that deal with the relationship with knowledge and in studies of Dayrell (1996, 2007, 2010, 2014) who consider the school as sociocultural space. The methodology is qualitative. We used as instrument of data collect semi-structured interviews with the students. Data analysis considered the three themes proposed by Charlot (2000): (a) the relationship of the identity that takes into account the learning process inserted in the history of the student; (B) the social relationship that structures the relationship with knowledge, considering the person as an individual inserted in a broader social history and (c) the epistemic relation to knowledge which defends that learning has different meanings for students, and as the sociocultural issue of school environment and the educational context that they were inserted. The results indicate that the identity construction that the individuals - young students and from the public school - make of themselfs in the world (school, family, society, work), directly influences the epistemic relations in the meaning of learning and consequently in the relationships that they make with biology contents that are build in the school context.
Keywords: Ensino de biologia; Relação com o saber; Escola sociocultural; Biology teaching; Relationship with knowledge; Sociocultural school; CIENCIAS BIOLOGICAS; CIENCIAS HUMANAS::EDUCACAO